2012
DOI: 10.3400/avd.oa.11.00094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Endovascular Abdominal Aortic Aneurysm Repair in Patients with Renal Insufficiency without Hemodialysis

Abstract: Objective: Chronic renal insufficiency may be a relative contraindication to endovascular aneurysm repair (EVAR) for the use of contrast enhanced mediums. It is thought that more contrast enhanced media are needed in patients who are not anatomically suitable for EVAR, because of procedural difficulties. We reviewed a 2 year EVAR experience at our institution to determine whether the procedure and use of contrast enhanced mediums has any deleterious effect on renal function in patients with pre-existing chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These results are in line with the literature data [41] and show that ''EVAR with contrast agents can be accomplished in patients with chronic renal insufficiency without hemodialysis; therefore, elevated creatinine levels may not be a contraindication in EVAR'' [41].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with the literature data [41] and show that ''EVAR with contrast agents can be accomplished in patients with chronic renal insufficiency without hemodialysis; therefore, elevated creatinine levels may not be a contraindication in EVAR'' [41].…”
Section: Discussionsupporting
confidence: 82%
“…These findings confirm conclusions of previous reports suggesting that elevated creatinine concentration and dialysis increase mortality risk disproportionate to respiratory and cardiac comorbidities. 5,13,14 Elevated creatinine concentration alone, however, conferred a slightly increased risk of 30-day mortality compared with dialysis in our multivariate regression model (OR, 3.36 vs 2.22). In examining the contribution of multiple comorbidities to mortality risk, renal and respiratory comorbidities in combination increased 30-day mortality risk by more than sevenfold.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have attempted to evaluate the effects of single risk factors that contribute to mortality after EVAR. 5,13,14,17 Given low mortality rates after EVAR, most previous studies have found small, statistically insignificant differences between high-risk and low-risk patients. A retrospective study by Mehta et al 13 stratified patients by serum creatinine concentration (<1.5 mg/dL, 1.5-2.0 mg/dL, and 2.1-3.5 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common found data concerns kidney complication after operations for AA in patients whose kidneys preoperatively were normal or were slightly altered. Here the post operative incidence of kidney failure for AA is 5.4% in patients with a normal kidney function; this incidence is multiplied by 2 or 3 amongst patients with a pre existing CKF (10)(11)(12). Mortality after kidney complication due to AA operation is very high and 25% to 66% (10-12).…”
Section: Discussionmentioning
confidence: 99%